A Literature Review on the Role of Financial Slack and Board Independence in the Relationship Between CEO Narcissism and Firm Performance (Third Sector Social Economic Review, 2026)
This study aims to examine the existing literature on the relationship between CEO narcissism and firm performance, explaining the role of financial slack and board independence in this relationship. The literature review includes 18 empirical studies published primarily in Web of Science and Scopus between 2007 and 2025, as the first empirical research on CEO narcissism began in 2007. The review found that existing studies in the literature on the impact of CEO narcissism on firm performance report inconsistent results. Researchers found that narcissistic CEOs increase performance through innovation or exorbitant investment decisions; on the other hand, CEO narcissism may also have negative impact on company performance due to behaviours such as financial manipulation, excessive risk taking, or consuming resources for personal image. Furthermore, it was noted that most studies were conducted using samples from developed countries, with limited research on developing countries. Moreover, the literature review revealed that financial slack and board independence have been the subject of only a limited number of studies. Financial slack plays a critical role in influencing the behaviour of CEOs with high levels of narcissism, whilst board independence is also important in terms of constraining such behaviour. The main contribution of this research is to draw attention to the research gaps in the existing literature on CEO narcissism and firm performance, thereby establishing a research agenda on the impact of CEO narcissism on firm performance.
Keywords: CEO narcissism; firm performance; financial slack; upper echelon theory; board independence